KawalPilkada: A Conceptual Secure ElectronicVote System Based Blockchain Technology - Herwanto, Riko; YA, Firmansyah (Politeknik Negeri Sriwijaya, 2020)
Â Today, elections are one of the foremost important means of sustaining democracies. thanks to the opportunities brought by technology, the need of creating the elections within the physical environment is decreasing every day. Instead, the difficulty of creating elections within the electronic environment is becoming more and more popular. With the emergence of Blockchain technology, the safety of the elections within the electronic environment has also been ensured to an excellent extent. On the opposite hand, moving the election system to the electronic environment will eliminate the physical costs, make sure the election security within the authoritarian regimes by eliminating the central authority through blockchain, and increase the participation rates within the elections because people can vote from anywhere with internet access. one of the foremost important elements within the blockchain-based electoral system is that the connection between the voter and therefore the vote, in other words, user privacy. during this article, we might wish to introduce an idea of blockchain- based voting systems